HISTORICAL TRENDS INFLUENCING THE FUTURE OF PERIOPERATIVE NURSING - Wade, Patricia (Operating Room Nurses Association of Canada Journal, 2012)
This paper explores the historical trends that have shaped the perioperative nursing specialty. The educational, societal, and political influences are examined through different historical periods. After, initially, being the first recognized nursing specialty operating room nursing was later removed from the nursing education curriculum. A debate as to whether perioperative nursing was simply a technical skill or actually “real” nursing was beginning and it continues to this day. Today, students’ lack of exposure to the operating room, unsuccessful preceptorship programs, and poor working conditions are creating major recruitment and retention challenges. Because these historical trends have led to the decline of perioperative nursing, it is crucial for modern nurses to understand the factors that are influencing our practice and to make collective efforts to positively influence the future of our specialty.